2021
DOI: 10.1249/mss.0000000000002678
|View full text |Cite
|
Sign up to set email alerts
|

Appetite and Energy Intake Regulation in Response to Acute Exercise

Abstract: PurposeThis study aimed to determine if energy intake and appetite regulation differ in response to an acute bout of resistance exercise (REx) versus aerobic exercise (AEx).MethodsPhysically inactive adults (n = 24, 35% ± 2% body fat, 50% female) completed three conditions: AEx (walking at 65%–70% heart rate max for 45 min), REx (1 set to failure of 12 exercises), and sedentary control (SED). Each condition was initiated in the postprandial state (35 min after breakfast). Appetite (visual analog scale for hung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, the present results revealed no significant compensation or meaningful change in daily EI after the different acute exercise interventions. This finding is in line with some previous acute (Stubbs et al, 2002a;Unick et al, 2010;Balaguera-Cortes et al, 2011;Vatansever-Ozen et al, 2011;Halliday et al, 2021) and chronic studies (Martins et al, 2010;Caudwell et al, 2013;Melzer et al, 2016;Castro et al, 2020), in that EI was almost unchanged after exercise interventions. In an early study by Whybrow et al (2008) energy intake only began to offset energy expenditure over an intervention during 1-2 weeks; that is, the energy intake not compensated immediately after exercise but changed imperceptibly in the following days.…”
Section: Energy Intake Appetite and Related Hormonessupporting
confidence: 92%
“…However, the present results revealed no significant compensation or meaningful change in daily EI after the different acute exercise interventions. This finding is in line with some previous acute (Stubbs et al, 2002a;Unick et al, 2010;Balaguera-Cortes et al, 2011;Vatansever-Ozen et al, 2011;Halliday et al, 2021) and chronic studies (Martins et al, 2010;Caudwell et al, 2013;Melzer et al, 2016;Castro et al, 2020), in that EI was almost unchanged after exercise interventions. In an early study by Whybrow et al (2008) energy intake only began to offset energy expenditure over an intervention during 1-2 weeks; that is, the energy intake not compensated immediately after exercise but changed imperceptibly in the following days.…”
Section: Energy Intake Appetite and Related Hormonessupporting
confidence: 92%
“…Several studies have also shown that aerobic exercise can alter plasma concentrations of PYY [50], PP [42], GIP [51], and leptin [52], though the impact of exercise on these hormones is transient. For example, PYY concentrations appear to be lower for only 90 min following exercise [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, self-reported dietary intake data are highly prone to misreporting and often unrelated to actual energy intake ( 40 ). The acute energy intake data for this trial are published elsewhere ( 25 , 26 ). Third, waking wear time was identified from the first and last instance of steps registered on the ActivPAL device.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a secondary analysis of a randomized crossover trial with three conditions designed to investigate the effect of exercise modality on appetite and energy intake ( 25 ). Data were collected between Fall 2017 and Spring 2019.…”
Section: Methodsmentioning
confidence: 99%